Towards comeniology as a science – the scientific and didactical workshop; research methodology - Sitarska, Barbara (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2019)
The article depicts John Amos Comenius’ selected ideas and their reference to the contemporary times. It is mainly based on his two major works: Great Didactics and Pampaedia, my own research papers and other available ones, as well as on some research conducted by education science students for their MA theses concerning John Amos Comenius’ teacher in reference to the modern teacher2. It focuses on Comenius’ idea of permanent education, which refers to contemporary education3. Nowadays permanent education is a key educational chal-lenge in Poland, Europe and all over the world. The article is an attempt to define comeniology as an emerging scientific discipline and specify the areas and ranges of comeniological research, mentioning its authors and describing their output published in “Siedlce Comeniological Research Bulletin. pedagogy series”. I prove the evolutional character of comeniological re-search. The article also mentions my education science students’ interest in Comenius and their activity including the research conducted for their MA theses about Comenius, presentations and written texts intended to be published in “Siedlce Comeniological Research Bulletin, peda-gogy series”.